Identification of the source of quasiperiodic VLF emissions using ground-based and Van Allen Probes satellite observations - Titova, E. E.; Kozelov, B. V.; Demekhov, A. G.; Manninen, J.; Santolík, O. (Ondřej); Kletzing, C. A.; Reeves, G. (Geophysical Research Letters, 2015)
We report on simultaneous spacecraft and ground-based observations of quasiperiodic VLF emissions and related energetic-electron dynamics. Quasiperiodic emissions in the frequency range 2-6kHz were observed during a substorm on 25 January 2013 by Van Allen Probe-A and a ground-based station in the Northern Finland. The spacecraft detected the VLF signals near the geomagnetic equator in the night sector at L=3.0-4.2 when it was inside the plasmasphere. During the satellite motion toward higher latitudes, the time interval between quasiperiodic elements decreased from 6min to 3min. We find one-to-one correspondence between the quasiperiodic elements detected by Van Allen Probe-A and on the ground, which indicates the temporal nature of the observed variation in the time interval between quasiperiodic elements. Multiscyrillicomponent measurements of the wave electric and magnetic fields by the Van Allen Probe-A show that the quasiperiodic emissions were almost circularly right-hand polarized whistler mode waves and had predominantly small (below 30°) wave vector angles with respect to the magnetic field.